Обнаружение представителя рода Halicyclops (Crustacea, Copepoda) в континентальной части Украины - Монченко, В.И.; Полищук, В.В. (Вестник зоологии, 1982)
Halicyclops cryptus secundus ssp. n. is described from a brackish well situated some 130 km from the Sea of Azov. T h e new subspecies differs from nomenotypic form by remarkably short innermost apical furcal seta (ca 10 times as short as outermost seta vs. 3.5-5 times in nomenotype), ratio of apical soines to distal endopode joint P4 (1.7 vs. 1.45-1:65) and other characters.